Деловните заедници и еко-етичките стандарди - Донев, Дејан (Аз-Буки, Скопје (Филозофско друштво на Македонија), 2006)
Today, the mankind is confronting with the biggest challenge till now – to save the nature from irreversible destroying. For this purpose, for a long time, the biggest attention is steered toward business units – as polluters and indicators of unstoppable grow. The question is: Can we do any kind of reorganization in these units without pressure and commands, with ethical and ecological awakens as a motivation and active power? For this aim we need to reinvestigate the whole perspective when we speak about the productivity and other things on the field of business! This must be pragmatic and also ethical – the pragmatism must be balanced with holistic thinking. In this meaning, the business and industry must follow certain ethical and ecological standards in evaluation and acting. These standards in business community must be bearers of one wholeness ethics of life.
Keywords: nature, ecological awakens, eco-ethics, pragmatism